Interfacing consciousness - Prentner, Robert; Hoffman, Donald D. (Frontiers in Psychology, 2024)
The current stage of consciousness science has reached an impasse. We blame the physicalist worldview for this and propose a new perspective to make progress on the problems of consciousness. Our perspective is rooted in the theory of conscious agents. We thereby stress the fundamentality of consciousness outside of spacetime, the importance of agency, and the mathematical character of the theory. For conscious agent theory (CAT) to achieve the status of a robust scientific framework, it needs to be integrated with a good explanation of perception and cognition. We argue that this role is played by the interface theory of perception (ITP), an evolutionary-based model of perception that has been previously formulated and defended by the authors. We are specifically interested in what this tells us about the possibility of AI consciousness and conclude with a somewhat counter-intuitive proposal: we live inside a simulation instantiated, not digitally, but in consciousness. Such a simulation is just an interface representation of the dynamics of conscious agents for a conscious agent. This paves the way for employing AI in consciousness science through customizing our interface.